Computational exploration of natural inhibitors against toxin-associated proteins in Naegleria fowleri Karachi strain. - Rabia, Faizan; Naveed, Muhammad; Bellido-Estévez, Inmaculada; Hanif, Nimra; Arshad, Arooj; Aziz, Tariq; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Alhomrani, Majid (Elsevier, 2025)
Naegleria fowleri, a thermophilic, free-living amoeba, is the causative agent of Primary Amoebic Meningoencephalitis (PAM), a rare but nearly always fatal brain infection. The rising number of PAM cases in Karachi, Pakistan, particularly linked to a unique local strain, underscores the urgent need for effective therapeutic interventions. In this study, a computational approach was employed to identify potential natural inhibitors targeting toxin-producing proteins from the N. fowleri Karachi strain. Eight exons encoding toxin proteins were retrieved from the Soft Berry Fgenesh 2.6 database, annotated using Gene Ontology tools, and subjected to physicochemical characterization. Hypothetical protein 4 was prioritized for molecular docking in the NF001 Karachi strain of Naegleria fowleri because it was identified through comparative mapping with previously known strains. Its function was predicted based on sequence alignment, suggesting that it may serve as a promising target for drug docking studies. Protein structures were predicted via AlphaFold2 and validated using MolProbity and Ramachandran plot analysis. Virtual screening of phytochemicals was conducted using PyRx, identifying himbacine as the most promising ligand with a binding affinity of –8.7 kcal/mol against hypothetical protein 4. Binding interactions were further confirmed using CB-Dock2, which revealed key binding residues involved in hydrogen bonding and hydrophobic interactions. ADMET profiling indicated that himbacine possesses favorable pharmacokinetics, non-toxicity, and high gastrointestinal absorption. Density Functional Theory (DFT) analysis showed a small HOMO-LUMO energy gap, indicating high reactivity and binding potential. Molecular dynamics simulations confirmed the structural stability of the protein-ligand complex over time. These findings suggest that himbacine, a plant-derived compound, holds promise as a safe and effective inhibitor against N. fowleri infections. However, further in vitro and in vivo studies are essential to validate its therapeutic potential.
https://openpolicyfinder.jisc.ac.uk/id/publication/15910?from=single_hit
Keywords: Biomedicina; Meningoencefalitis; Amebas; Enfermedades por protozoos; Naegleria fowleri; Brain-eating amoeba; Computational drug design; Himbacine ADMET analysis; Molecular docking